Implementation of Business Strategy during the Covid-19 Pandemic - Siti Saleha; Zuhrinal M. Nawawi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study was conducted to determine the business strategies implemented by Micro, Small and Medium Enterprises (MSMEs) in dealing with the COVID-19 pandemic. The object of research is the snack food industry with the trademark Waroenk Ngemil which is located on Jalan Sadang, Bandung Regency. The method used is a qualitative research method with a descriptive approach. Based on the results of the study, data were obtained that the business strategy in marketing their products was through social media. From the results of the research above, it can be described that this strategy can work as expected by taking into account the purchasing power of consumers during this covid-19 pandemic. However, by using social media facilities, the funds needed by small business actors have an impact on reducing business capital. From the description above, it can be concluded that the role of government and banking is very important, especially with regard to training in the use of information technology so that small business products can survive in the midst of the COVID-19 pandemic.